Design issues for net zero-energy buildings - Aelenei, Laura Elena (2013)
Net Zero-Energy Buildings (NZEBs) have received increased attention in recent years as a result of constant concerns for energy supply constraints, decreasing energy resources, increasing energy costs and rising impact of greenhouse gases on world climate. Promoting whole, building strategies that employ passive measures with energy efficient systems and technologies using renewable energy, became a European political strategy since the publication of the Energy Performance of Building Directive recasr in May 2010 by the European Parliament and Council.